2006
DOI: 10.1111/j.1462-5822.2005.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Shiga toxin versus H7 flagellin in enterohaemorrhagic Escherichia coli signalling of human colon epithelium in vivo

Abstract: SummaryEnterohaemorrhagic Escherichia coli O157:H7 (EHEC) is a clinically important foodborne pathogen that colonizes human colon epithelium and induces acute colonic inflammation, but does not invade the epithelial cells. Whereas Shiga toxin (Stx) and bacterial flagellin have been studied for their ability to upregulate the production of proinflammatory chemokines by cultured human colon cancer cell lines, the relevance of studies in colon cancer cell lines to the production of proinflammatory signals by norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 56 publications
7
88
1
Order By: Relevance
“…Some occasional cells in normal tissue showed STxB labeling. These cells may correspond to the colonic myofibroblasts described by others (15), and this finding could explain, at least in part, that some Gb 3 was detected in normal intestinal tissue, as described above. Tumor cells arranged in glandular structures clearly showed STxB labeling (Fig.…”
Section: Gb 3 Is Expressed In Human Colorectal Cancer and Liver Metasmentioning
confidence: 81%
See 1 more Smart Citation
“…Some occasional cells in normal tissue showed STxB labeling. These cells may correspond to the colonic myofibroblasts described by others (15), and this finding could explain, at least in part, that some Gb 3 was detected in normal intestinal tissue, as described above. Tumor cells arranged in glandular structures clearly showed STxB labeling (Fig.…”
Section: Gb 3 Is Expressed In Human Colorectal Cancer and Liver Metasmentioning
confidence: 81%
“…Several studies showed that human intestinal epithelium (11,15) and purified epithelial cells (12,33,34) were Gb 3 -negative. In agreement with these studies, we found that normal human colonocytes were not labeled by STxB, and in our previous in vivo experiments on mice, STxB did not accumulate in these cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…A further complication of the commonly used human polarized intestinal cell lines is that the cellular localization of TLR5 in the various cell types appears to be different. In some cells (such as T84) TLR5 appears to be expressed solely at the basolateral cell surface (Gewirtz et al, 2001), while in other cell lines (such as Caco-2) and in colon xenografts in vivo, TLR5 is also expressed at the apical membrane (Bambou et al, 2004;Cario and Podolsky, 2000;Miyamoto et al, 2006). As under natural conditions intestinal epithelial cells will be most frequently exposed to flagellin from the luminal side, we added flagellin to the apical side of mIC cl2 cells in this study, although we noted similar responses to flagellin when the flagellin was applied from the basolateral side.…”
Section: Discussionmentioning
confidence: 99%
“…EHEC is able to specifically interact with human colonic xenografts, inducing A/E lesions and tissue damage dependent on a functional T3SS (Golan et al 2011). This type of model has also been used to show that H7 flagellin is a major factor involved in increases of proinflammatory chemokines in response to EHEC infection (Miyamoto et al 2006). An advantage of this model is the ability to study the immunogenic reaction of A/E pathogens in the absence of other microbial products.…”
Section: In Vivo Infection Modelsmentioning
confidence: 99%